Efektifitas Model Flipped Classroom dalam Mata Kuliah Perencanaan Pembelajaran Prodi S1 PGMI UMSIDA - Ida Rindaningsih (Proceedings of The ICECRS, 2018)
This research was conducted at the Faculty of Islamic studies in the planning of the courses of instruction. Research using a sample of 94 respondents consisting of Prodi PAI, PGMI, and PBA. Types of quantitative research using path analysis. The findings in this study are learning with the Flipped Classroom make meetings in a more effective and meaningful class. Students may compose an RPP in accordance with their respective speeds, flexible but responsibly, and have the freedom to obtain in-depth study based on the processed data acquisition and projects that are being done outside of the classroom. The results of the analysis showed a strong relationship between the model flipped classroom, teaching style, motivation and interest in learning to learning outcomes i.e. form RPP. Overall results show that the minimum hours of lectures and practical limitations on MK Planning Learning can be used as classroom flipped the model strategies are effective in maximizing the responsibility students dig learning materials online so support the motivation and interest in producing the project.